Danų kalbos gramatika / Danish Grammar - Spraunienė, Birutė (Scandinavistica Vilnensis, 2019)
This book is a Danish grammar for Lithuanian students from beginner to upper intermediate level. It contains a description of Danish word classes, forms of inflection and usage, information about the Danish sentence structure, various constructions as well as essential punctuation rules. In order to explain different grammar topics, many examples of the Danish usage are given and translated into Lithuanian.  Ši knyga – tai praktinė gramatika, skirta besimokantiems danų kalbos (A1–B2 mokėjimo lygiai). Joje išsamiai aprašomos danų kalbos dalys, jų kaitymas ir vartojimas, sakinių sudarymas, įvairios konstrukcijos, pateikiamos pagrindinės skyrybos taisyklės. Aptariami kalbos reiškiniai iliustruojami danų kalbos pavyzdžiais, greta pateikiamas lietuviškas vertimas.
Keywords: Danish grammar; Learner’s grammar